1993
DOI: 10.1007/bf00180056
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated antigens in effusions of malignant and benign origin

Abstract: We determined the concentration and effusion/serum ratio of mucin-like carcinoma-associated antigen (MCA) in comparison to carcinoembryonic antigen, carbohydrate antigen 19-9, cancer antigen 125, and cancer antigen 15-3 in 80 sera and 99 effusions from 64 patients with histologically confirmed malignancies (4 patients out of this group showed various effusions simultaneously, which were analyzed separately) and 31 patients with various nonneoplastic diseases. Tumor cells were detected by cytological examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
1
8
2
Order By: Relevance
“…This is in contrast to two studies 6,18 where higher mean CA-15.3 values were found for effusions from breast carcinoma rather than other carcinomas, especially lung. 18 No differences were noted in this study in CA-15.3 levels between cytologically positive and cytologically negative malignant effusions in contrast to those reported by Ammon et al 1 Overall, superior sensitivity of CA-15.3 over CEA in effusions was noted by Ammon, 1 Kandylis 6 and Neskovic. 12 Neskovic 12 also described higher levels of CA-15.3 in effusions from breast carcinoma in patients who responded to chemotherapy.…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…This is in contrast to two studies 6,18 where higher mean CA-15.3 values were found for effusions from breast carcinoma rather than other carcinomas, especially lung. 18 No differences were noted in this study in CA-15.3 levels between cytologically positive and cytologically negative malignant effusions in contrast to those reported by Ammon et al 1 Overall, superior sensitivity of CA-15.3 over CEA in effusions was noted by Ammon, 1 Kandylis 6 and Neskovic. 12 Neskovic 12 also described higher levels of CA-15.3 in effusions from breast carcinoma in patients who responded to chemotherapy.…”
contrasting
confidence: 56%
“…4,12 However, falsely elevated serum levels, above 30 µm/mL, are seen in patients with benign breast diseases. 4 CA-15.3 has also been measured in effusion fluid, with varying sensitivity, for the overall detection of malignant effusions 1,2,6,12,18,19 as well as those secondary to breast carcinoma. 1,2,6,12,18 Some studies have indicated the superior sensitivity of the CEA assay over CA-15.3 content in the detection of malignant effusions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Therefore, a specific cytological diagnosis may have a sensitivity of only 40-80%. [6][7][8] Samples that are inconclusive because of some cellular atypia can be further evaluated with ancillary morphological methods, such as immunocytochemistry 1-3 9 and DNA cytometry, 2 9 10 although these techniques are of little help when only a few preserved tumour cells are present.Biochemical parameters, such as the concentrations of carcinoembryonic antigen (CEA) 6-8 10-12 and cholesterol 4 12-15 in the serous eVusion, have been studied as markers of malignancy. Such assays can be done rapidly in properly preserved eVusions after cytological examination, but their diagnostic value is still debated.…”
mentioning
confidence: 99%
“…5 Therefore, a specific cytological diagnosis may have a sensitivity of only 40-80%. [6][7][8] Samples that are inconclusive because of some cellular atypia can be further evaluated with ancillary morphological methods, such as immunocytochemistry 1-3 9 and DNA cytometry, 2 9 10 although these techniques are of little help when only a few preserved tumour cells are present.…”
mentioning
confidence: 99%